Mineralogical and Geochemical studies of Eocene Carbonate rocks at East El- Minia Governorate, Egypt - Ammawy, Mahmoud A. El; Hewaidy, Abdel Galil A.; Moussa, Bothaina M.; Abd el Hafz, Nabil A.; El Abd, El Sayed A. (Journal of Himalayan Earth Sciences, 2023)
The present work is mainly concerned with the Mineralogical and geochemical studies on the Eocene rocks exposed at East El- Minia Ggovernorate. The study area is located on the eastern side of the Nile Valley between Maghagha City and Mallawi City. It is located between lat. 27°42’7"N and 28°41’30"N and long. 30°43’15"E and 31°30’E. The study areas, are represented by five formations namely; Minia (Lower Eocene), Samalut, Maghagha and Qarara (Middle Eocene) and El Fashn (Middle – Late Eocene) Formations. The mineral component shows that the Eocene carbonates were deposited in an alkaline environment that was close to a landmass that provided quartz and clay to the environment. Limestone chemical characters reveals that; Eocene limestones were mostly deposited under relatively warm alkaline conditions. However the pH degree of alkalinity during the Minia, Samalut and Maghagha formations (less in SiO2 than that prevailed during the El Fashn Formation times.